Usefulness of Canadian Public Health Insurance Administrative Databases to Assess Breast and Ovarian Cancer Screening Imaging Technologies for BRCA1/2 Mutation Carriers. Issue 4 (November 2016) - Larouche, Geneviève; Chiquette, Jocelyne; Plante, Marie; Pelletier, Sylvie; Simard, Jacques; Dorval, Michel
Purpose: In Canada, recommendations for clinical management of hereditary breast and ovarian cancer among individuals carrying a deleterious BRCA1 or BRCA2 mutation have been available since 2007. Eight years later, very little is known about the uptake of screening and risk-reduction measures in this population. Because Canada's public health care system falls under provincial jurisdictions, using provincial health care administrative databases appears a valuable option to assess management of BRCA1/2 mutation carriers. The objective was to explore the usefulness of public health insurance administrative databases in British Columbia, Ontario, and Quebec to assess management after BRCA1/2 genetic testing. Methods: Official public health insurance documents were considered potentially useful if they had specific procedure codes, and pertained to procedures performed in the public and private health care systems. Results: All 3 administrative databases have specific procedures codes for mammography and breast ultrasounds. Only Quebec and Ontario have a specific procedure code for breast magnetic resonance imaging. It is impossible to assess, on an individual basis, the frequency of others screening exams, with the exception of CA-125 testing in British Columbia. Screenings done in private practice are excluded from the administrative databases unless covered by special agreements for reimbursement, such as all breast imaging exams in Ontario and mammograms in British Columbia and Quebec. There are no specific procedure codes for risk-reduction surgeries for breast and ovarian cancer. Conclusion: Population-based assessment of breast and ovarian cancer risk management strategies other than mammographic screening, using only administrative data, is currently challenging in the 3 Canadian provinces studied.